ANALISIS STRUKTUR BIAYA DAN EFISIENSI PADA AGROINDUSTRI BAWANG GORENG â€œUD. SRI REJEKIâ€ DI KOTA PALU PROVINSI SULAWESI TENGAH - Hisky A. Rantung; Caroline B.D. Pakasi; Celcius Talumingan (COCOS, 2015)
ABSTRACK This study aimed to analyze the cost structure and efficiency in agroindutri Fried Onions "UD. Sri Rejeki "is seen from the data such as the cost of production, Production Cost Ratio, business efficiency and Break even point. Based on these results it can be concluded that the UD. Sri Rejeki is a little fried onions management industry which was to have the meuju to 26 workers. The main raw materials used come from the original red onions from Palu valley. The resulting product fried onions packed in various packaging sizes. Product marketing reach of UD. Sri Rejeki is quite extensive, namely in the city of Palu, then fried onion has penetrated several large supermarkets such as Hero Carrfour, Giant Jakarta and Makassar Alfa. The research analyzes the cost structure and efficiency based on data monthly from production activities. Thus it is known that the reception is Rp 517.500.000 per month. Cost structure consists of fixed costs and variable costs Rp2.858.127,7 Rp Rp154.815.000 that form the production cost Rp 157,673,173.7. Seeing the structure of these costs can be known at what the costs are borne for the monthly production process so as to make plans. Then look at the efficiency of production of the business is also included in the criteria for a profitable business because the value of the ratio resulting from the analysis of production efficiency is thus the value 3.3 R / C> 1. Judging from the analysis Break even point, business of UD. Sri Rejeki is said to have reached the break- even point is the production of 2436 kg and can be said reach the break-even point attempt at the value of Rp 234.280 perkg. Keywords: Cost Structure, Production Efficiency, BEP